Silver-blend hydroxyapatite bio-ceramics for enhanced photocatalytic degradation of methylene blue - Manoj V. Junnarkar; Prateek V. Sawant; Mahadev A. Parekar; Avadhut V. Kardile; Ashish B. Thorat; Ramakant P. Joshi; Ravindra U. Mene (Academia Materials Science)
In this article, nanostructured hydroxyapatite (HAp) and Ag-doped HAp are synthesized via a wet chemical precipitation route and ion-exchange methods to analyze their photocatalytic performance via the degradation of organic dyes. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscope (SEM)/energy-dispersive X-ray spectroscopy (EDS) are used to analyze the structural, functional, morphological, and elemental properties of the samples. Ultra violet (UV)-visible diffuse reflectance spectroscopy is used to monitor the changes in the band-gap energies of the samples. The Tauc plots show the decrease in the band gap of HAp due to Ag doping. XRD confirms the crystalline hexagonal phase of HAp, whereas the SEM and EDS further confirm the presence of Ag ions in the HAp matrix. FTIR spectra validate the characteristic bands of hydroxyl and phosphate species of HAp. The degradation of organic dyes through photocatalysis was carried out using pure and Ag-doped HAp samples as the catalysts under solar irradiation. It is observed that the Ag-HAp photocatalysts show a better efficiency toward the degradation of methylene blue (MB) compared to malachite green or Rhodamine B. HAp sample with Ag (0.15 M) content showed a remarkable degradation of MB (97% in 60 minutes) when compared to pure HAp, which showed only 11% degradation. The effect of Ag doping on the reaction kinetics was also studied, wherein the reaction rates were enhanced by increasing Ag concentrations. Moreover, the Ag-doped HAp shows excellent recycling ability highlighting its practical usage as a photocatalyst for wastewater treatment.